Analisis Kepuasan Pasien Rawat Jalan RSUD Sylvani: Pengaruh Kualitas Pelayanan Terhadap Indeks Kepuasan Pasien - Sugianto Sugianto; Alamsyah Alamsyah; Susanna Halim (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to analyze outpatient satisfaction at Sylvani Hospital by considering the factors that influence it. The research method used was a quantitative survey with a cross-sectional research design, meaning data were collected at a single point in time to capture a snapshot of patient satisfaction levels and the factors affecting them. The cross-sectional approach enabled the researchers to analyze relationships between service quality dimensions and patient satisfaction within a limited timeframe. Data were collected from 205 respondents selected using sampling techniques in a limited population. The results showed that of the five dimensions of service quality (reliability, assurance, physical evidence, empathy, and responsiveness), the dimensions of tangible and responsiveness had a significant influence on patient satisfaction. This study recommends improving physical facilities and implementing a service digitization system to increase patient satisfaction